Labyrinthitis: Comprehensive Literature Review Of Inner Part Ear Infection - Rafi Gutra Aslam; Putu Ristyaning Ayu Sangging; Rani Himayani (Medula, 2023)
Labyrinthitis (Internal otitis) is an inflammation process of the ear labyrinth located in the inner part of the ear. Labyrinthitis has distinctive symptoms that combine from hearing ability and balance disturbance that cause  sensorineural type deafness and vertigo. This paper uses the literature review method as a  chosen method that chooses from bibliographic that last 15 years ago to discuss comprehensively about labyrinthitis. Labyrinthitis  is a condition that generally happens in elder age because the disturbance of the vestibulocochlear system  that has similarity with other health problem such as Ménière disease, patient history and advance examination comprehensively needed to rule out labyrinthitis with another health related to balance and hearing  problem. Labyrinthitis prognosis is bonam if treatment occurs as soon as possible and there is no expansion found into another region adjacent to the ear structure that potentially cause severe complication. Despite of severe complication is rare in post-antibiotic era, complication  could still happen in few patient and become life threatening problem because of it’s site adjacent with brain anatomy structure, therefore treatment could  be given to the patient with this condition. Further research need to discuss about another therapy option that available to treat the Labyrinthitis from every classification such as viral, bacteria, autoimmune, immunodeficiency, ossificant, and even the recent one associated with COVID-19 pandemic.